Analisis PDRB Provinsi Lampung dan Pengaruhnya Terhadap PDB Nasional Periode 2011-2015 - Hidayat, Robist (Sosio e-Kons, 2019)
This study aims to analyze the gross regional domestic product in Lampung province. As for what is being analyzed is whether there is any influence from Lampung province's GRDP with the national GDP. With the data taken namely 5 years starting in 2011-2015. By using the literature review method and analyzing existing data, it continues to be developed into a new analysis by not ruling out existing methods. The results of this study are that the GDP of each province is different so it does not become a reference in the effect of national GDP in implication.